Influence of land-use change and season on soil greenhouse gas emissions from a tropical wetland: A stepwise explorative assessment - Ondiek, Risper Ajwang'; Hayes, Daniel S.; Kinyua, Damaris Njeri; Kitaka, Nzula; Lautsch, Erwin; Mutuo, Paul; Hein, Thomas (Elsevier, 2021)
Tropical wetlands are important climate regulators. However, their climate regulating function is at risk by land-use conversion for agricultural purposes. In sub-Saharan Africa, studies investigating the effect of land-use change in wetlands and associated soil greenhouse gas (GHG) emissions remain limited. Moreover, the influence of season in GHG emissions with land-use change has hardly been studied. Therefore, we investigated methane (CH4), carbon dioxide (CO2), and nitrous oxide (N2O) emissions from a Kenyan wetland and adjacent areas converted to farmland during the dry and rainy seasons. Moreover, we assessed which soil parameters drive the variations in GHG emissions. The GHG samples were collected by the static chamber method and analyzed by gas chromatography. For data analysis, we employed an explorative-statistical approach to explain the emission rates' variation and determine which parameters influence the GHG emissions, both as main and interaction effects. The results showed that regardless of the season, there were CH4 emissions (>0.50 mg m−2 h−1) from the wetland when soil organic carbon content was high and uptake (<0.001 mg m−2 h−1) when both soil organic carbon content and soil moisture were low. In the farmland, there was CH4 uptake when soil nitrate‑nitrogen content was high. CO2 emissions did not vary significantly between the land-use types. Instead, emission rates were primarily governed by season. The highest emissions (>175 mg m−2 h−1) during the dry season were attributed to high soil organic carbon content. During the rainy season, emissions hardly exceeded 175 mg m−2 h−1. Regarding N2O, we detected the highest emissions (>5 μg m−2 h−1) from the farmland during the dry season. Overall, this study shows that wetland conversion to farmland encourages CH4 uptake regardless of the season and increases N2O emissions during the dry season. Based on the respective GHG global warming potential, these patterns may pose an increased environmental threat.